2010
DOI: 10.1128/aac.00715-09
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae AcrAB Efflux Pump Contributes to Antimicrobial Resistance and Virulence

Abstract: Respiratory infections caused by Klebsiella pneumoniae are characterized by high rates of mortality and morbidity. Management of these infections is often difficult, due to the high frequency of strains that are resistant to multiple antimicrobial agents. Multidrug efflux pumps play a major role as a mechanism of antimicrobial resistance in Gram-negative pathogens. In the present study, we investigated the role of the K. pneumoniae AcrRAB operon in antimicrobial resistance and virulence by using isogenic knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
254
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(272 citation statements)
references
References 43 publications
11
254
2
5
Order By: Relevance
“…This is an important example that establishes a link between antibiotic resistance and AcrABTolC-mediated virulence in S. enterica. Padilla et al also showed that a K. pneumoniae acrAB knockout mutant exhibited a lower capacity than the wild-type strain to cause pneumonia in a murine model (90). Bialek et al found that overexpression of the AcrAB efflux system in the Caenorhabditis elegans model is linked to an increased virulence potential in K. pneumoniae (91).…”
Section: Ribosomal Protection Tet44mentioning
confidence: 95%
“…This is an important example that establishes a link between antibiotic resistance and AcrABTolC-mediated virulence in S. enterica. Padilla et al also showed that a K. pneumoniae acrAB knockout mutant exhibited a lower capacity than the wild-type strain to cause pneumonia in a murine model (90). Bialek et al found that overexpression of the AcrAB efflux system in the Caenorhabditis elegans model is linked to an increased virulence potential in K. pneumoniae (91).…”
Section: Ribosomal Protection Tet44mentioning
confidence: 95%
“…The role of efflux in colistin resistance is not well understood, but several studies suggested the involvement of efflux pumps in colistin resistance. Mutations in kpnEF and acrAB, encoding components of efflux pumps, may actually lead to a 2-fold decrease of the MIC of colistin and increase bacterial survival in the presence of a low concentration of polymyxins (163,164). Addition to the test medium of low doses of the efflux pump inhibitor carbonyl cyanide m-chlorophenylhydrazone (CCCP) decreased the MICs for resistant strains (128-to 512-fold reductions) and partially or completely inhibited the regrowth of resistant subpopulations (165).…”
Section: Other Mechanisms Contributing To Polymyxin Resistance In Entmentioning
confidence: 99%
“…A Salmonella acrB mutant strain showed decreased invasion and survival in mouse monocyte macrophages (Buckley et al, 2006). Klebsiella pneumoniae AcrAB contributes to resistance to antimicrobial peptides, and an AcrB knockout mutant exhibited a reduced capacity to cause pneumonia in a murine model (Padilla et al, 2010). The acrAB regulation mechanism must be examined to understand the physiological role of AcrAB.…”
Section: Introductionmentioning
confidence: 99%